Introduction: Echoes of Revolutions, Uprisings, Social Movements, and Protests: Historiographical Trajectories and Interpretive Approaches - Michalelli, Maria; Papachristou, Maria (Mos Historicus: A Critical Review of European History, 2024)
An introduction to Mos Historicus: A Critical Review of European History's second issue.